Candrakīrti’s theory of perception: A case for non-foundationalist epistemology in Madhyamaka - Thakchoe, Sonam (Acta Orientalia Vilnensia, 2010)
University of Tasmania Some argue that Candrakīrti is committed to rejecting all theories of perception in virtue of the rejection of the foundationalisms of the Nyāya and the Pramāṇika. Others argue that Candrakīrti endorses the Nyāya theory of perception. In this paper, I will propose an alternative non-foundationalist theory of perception for Candrakīriti. I will show that Candrakrti’s works provide us sufficient evidence to defend a typical Prāsagika’s account of perception that, I argue, complements his core non-foundationalist ontology.